2021
DOI: 10.1093/molbev/msab354
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Cryptic Pseudogenization in Penguin Toll-Like Receptors

Abstract: Penguins (Sphenisciformes) are an iconic order of flightless, diving seabirds distributed across a large latitudinal range in the Southern Hemisphere. The extensive area over which penguins are endemic is likely to have fostered variation in pathogen pressure, which in turn will have imposed differential selective pressures on the penguin immune system. At the front line of pathogen detection and response, the Toll-like receptors (TLRs) provide insight into host evolution in the face of microbial challenge. TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 102 publications
(199 reference statements)
2
13
0
Order By: Relevance
“…Several of these genes might be under positive selection corresponding to host-pathogen coevolution. For instance, we confirm previous reports 53,54 that the bacterial-recognizing Toll-like receptors TLR4 and TLR5 (Figs. 4a and 5b) are positively selected in penguins.…”
Section: Resultssupporting
confidence: 92%
“…Several of these genes might be under positive selection corresponding to host-pathogen coevolution. For instance, we confirm previous reports 53,54 that the bacterial-recognizing Toll-like receptors TLR4 and TLR5 (Figs. 4a and 5b) are positively selected in penguins.…”
Section: Resultssupporting
confidence: 92%
“…Sharma et al, 2020). Other lineage-specific gene loss events within specific clades of birds have also been identified (Fiddaman et al, 2022;Friocourt et al, 2017;Haimson et al, 2021;Huang et al, 2022;Wicher and Fries, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…However, a study in chicken has shown that activation of TLR15 involves proteolytic cleavage of the LRR ectodomain ( de Zoete et al 2011 ), suggesting that genetic variation in this domain could be functionally neutral. In addition, TLR15 has been revealed to cryptically pseudogenize in some birds ( Fiddaman et al 2021 ) which could partially explain the high sequence variation detected in this gene. We did, however, not detect any signs of pseudogenization of TLR15 in the mallard genome, and a test for relaxation of selection pressure (implemented in Datamonkey) on TLR15 in the mallard versus all other investigated taxa was not significant ( K = 0.62, P = 0.67, LR = 0.18).…”
Section: Resultsmentioning
confidence: 99%